Liquid cooling based on thermal silica plate for battery thermal management system. (26th July 2017) - Wang, Cong; Zhang, Guoqing; Meng, Like; Li, Xinxi; Situ, Wenfu; Lv, Youfu; Rao, Mumin
Summary: To achieve safe, long lifetime, and high‐performance lithium‐ion batteries, a battery thermal management system (BTMS) is indispensable. This is especially required for enabling fast charging‐discharging and in aggressive operating conditions. In this research, a new type of battery cooling system based on thermal silica plates has been designed for prismatic lithium‐ion batteries. Experimental and simulations are combined to investigate the cooling capability of the BTMS associated to different number of cooling channels, flow rates, and flow directions while at different discharge C‐rates. Results show that the maximum temperature reached within the battery decreases as the amount of thermal silica plates and liquid channels increases. The flow direction had no significant influence on the cooling capability. While the performance obviously improves with the increase in inlet flow rate, after a certain threshold, the gain reduces strongly so that it does not anymore justify the higher energy cost. Discharged at 3 C‐rate, an inlet flow rate of 0.1 m/s was sufficient to efficiently cool down the system; discharged at 5 C‐rate, the optimum inlet flow rate was 0.25 m/s. Simulations could accurately reproduce experimental results, allowing for an efficient design of the liquid‐cooled BTMS. Abstract : 1 A new type of battery cooling system based on thermal silica plates has been designed for lithium‐ion batteries. 2 The cooling capability of the battery thermal management system associated to different number of cooling channels, flow rates, and flow directions at different discharge current density is investigated by experiment and simulation. 3 Considering the certain channel number design and inlet flow rate, the flow direction was demonstrated by experiment to play an insignificant role on the cooling performance.